Development and validation of a high-performance liquid chromatographic method for bioanalytical application with rimonabant - Bhaumik, Uttam; Ghosh, Animesh; Chatterjee, Bappaditya; Sengupta, Pinaki; Darbar, Soumendra; Roy, Bikash; Nandi, Utpal; Pal, Tapan K. (Elsevier, 2009)
A simple and feasible high-performance liquid chromatographic method with UV detection was developed and validated for the quantiﬁcation of rimonabant in human plasma. The chromatographic separation was carried out in a Hypersil BDS, C18 column (250 mm×4.6 mm; 5m). The mobile phase was a mixture of 10 mM phosphate buffer and acetonitrile (30:70, v/v) at a ﬂow rate of 1.0 ml/min. The UV detection was set at 220 nm. The extraction recovery of rimonabant in plasma at three quality control (QC) samples was ranged from 84.17% to 92.64%. The calibration curve was linear for the concentration range of 20–400 ng/ml with the correlation coefﬁcient (r 2 ) above 0.9921. The method was speciﬁc and sensitive with the limit of quantiﬁcation of 20 ng/ml. The accuracy and precision values obtained from six different sets of QC samples analyzed in separate occasions ranged from 88.13% to 106.48% and 0.13% to 3.61%, respectively. In stability tests, rimonabant in human plasma was stable during storage and assay procedure. The method is very simple, sensitive and economical and the assay was applied to human plasma samples in a clinical (pharmacokinetic) study of rimonabant.